SUPPLY CHAIN ANALYSIS OF DISPOSABLE MEDICAL DEVICES - Hery Suliantoro1, Intan Novita Dewi Naniek Utami Handayani (USIM, THAMKAM, KHON KAEN, UMY, 2016)
As a middle-income countries, pharmaceutical cost in Indonesia is high in both public and private sectors. One of pharmaceutical services cost in Indonesia is disposable medical device. Disposable medical device are medical devices intended for single-use and are used to support the treatment process. The price of disposable medical devices in Indonesia may varies, but it should be a concern if there is different price for the same product. There are difference price of disposable medical devices between conventional procurement system and e-catalogue procurement system. This study is conducted to determine the supply chain of disposable medical devices from the two procurement systems that is in the strategic quadrant. From the study with Kraljic Portfolio Matrix methods, disposable medical devices chosen are disposable syringe 5cc. The result of study, the supply chain procurement of e-catalogue system is shorter than conventional procurement system. Shorter supply chain led to less purchase price of disposable syringe 5cc. By using e-catalogue system, the procurement process will be easier and faster. Keywords :supply chain, kraljic portfolio matrix, disposable medical devices